Anthelmintic effect of Zingiber purpureum infuse and extract on adult worms of Haemonchus contortus in vitro - ., Beriajaya; Murtiadi, T.B.; Herawaty, Murti (Indonesian Journal of Animal and Veterinary Sciences, 1998)
The aim of this study is to determine anthelmintic effect of âbangleâ (Zingiber purpureum) on adult worms of Haemonchus contortus in vitro. Bangle were washed and cut into small pieces, and then put into oven with temperature of not more than 50oC for 4 days. Furthermore, it was grained with a mesh of 0.75 mm into a form of powder. Infuse was made by mixing a powder of âbangleâ with 100 ml distill water on beaker glass and then heat on water bath for 30 minutes at temperature of 90oC. It was made at a concentration (w/v) of 0%, 2.5%, 5%, 10%, 20% and 40%. Extract was made by percolation with methanol until filtrate produced, and this filtrate was condensed with rotapavor at 48oC with rotated at 200 rpm. Extract were made into a concentration (w/v) of 0%, 0.5%, 1%, 2%, 4% and 8%. Ten adult worms of H. contortus in Petri-dish were dipped with infuse or extract at each concentration with 5 replication. Observations were made every 30 minutes for a period of 6 hours to determine whether the adult worms were still alive or death. Faeces from donor of sheep artificially infected with H. contortus were cultured in vermiculite with infuse or extract used to keep humidity. Each treatment was repeated 5 times. Observations were made at the end of experiment to calculate on the total number infective larvae. The results showed that infuse or extract of âbangleâ have anthelmintic effect on H. contortus. The form of extract showed a better effect compared with infuse at a concentration of 0.5% and 2.5% respectively. The increase of concentration will result in a better effect. Key words : Haemonchus contortus, Zingiber purpureum, âbangleâ